The Bransfield current system - Sangrà, Pablo; Gordo Rojas, Carmen; Hernández-Arencibia, Mónica; Marrero Díaz, Ángeles; Rodríguez-Santana, Ángel; Stegner, Alexander; Martínez Marrero, Antonio; Pelegrí, Josep L.; Pichon, Thierry (Deep Sea Research Part I: Oceanographic Research Papers, 2011)
We use hydrographic data collected during two interdisciplinary cruises, CIEMAR and BREDDIES, to describe the mesoscale variability observed in the Central Basin of the Bransfield Strait (Antarctica). The main mesoscale feature is the Bransfield Front and the related Bransfield Current, which flows northeastward along the South Shetland Island Slope. A laboratory model suggests that this current behaves as a gravity current driven by the local rotation rate and the density differences between the Transitional Zonal Water with Bellingshausen influence (TBW) and the Transitional Zonal Water with Weddell Sea influence (TWW). Below the Bransfield Front we observe a narrow (10 km wide) tongue of Circumpolar Deep Water all along the South Shetland Islands Slope. At the surface, the convergence of TBW and TWW leads to a shallow baroclinic front close to the Antarctic Peninsula (hereafter Peninsula Front). Between the Bransfield Front and the Peninsula Front we observe a system of TBW anticyclonic eddies, with diameters about 20 km that can reach 300 m deep. This eddy system could be originated by instabilities of the Bransfield Current. The Bransfield Current, the anticyclonic eddy system, the Peninsula Front and the tongue of Circumpolar Deep Water, are the dynamically connected components of the Bransfield Current System.